Estimating effects of individual-level workplace mental wellbeing interventions: cross-sectional evidence from the UK - Fleming, W (Wellbeing Research Centre, 2023)
Promotional mental health interventions have become increasingly common in British workplaces but evaluative research lacks methodological quality, adequate sample size, or is more concerned with economic outcomes than employee health. Recently, a critical scholarship has emerged in sociology that questions the labour and health politics of workplace ‘wellness’. This article presents quantitative research addressing these concerns by estimating the ‘treatment effect’ of mental health programmes using clustered Bayesian propensity score analysis with the ‘Britain’s Healthiest Workplace’ survey – a sample of 143 British organisations and 27,932 workers. The analysis estimates the effect of a range of common initiatives including: mindfulness, resilience training, stress management and wellbeing apps. No evidence is found to demonstrate that these strategies improve worker mental health across multiple employee mental health measures. This suggests that recent critical literature is right to be concerned and that convenient well-being strategies should be given less financial and institutional support.